2020
DOI: 10.3390/brainsci10060386
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and Alzheimer’s Disease Risk: A Meta-Meta-Analysis

Abstract: Background: Alzheimer’s disease (AD) is the most common subtype of dementia. In the last ten years, the relationship between cholesterol and AD has been investigated. Evidence suggests that cholesterol is associated with AD and represents promising targets for intervention. However, the causality of these associations is unclear. Therefore, we sought to conduct a meta-meta-analysis to determine the effect of cholesterol on the development AD. Then, we assessed the effect of serum levels of low-density lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 58 publications
4
59
0
Order By: Relevance
“…In addition, likely to this study, the improvement of cholesterol level was observed by administering propolis to rats, which supports and is consistent with the results of this study [ 24 ]. In the same paper, the inhibitory effect of hydroxymethylglutaryl-CoA (HMG-CoA) reductase, a cholesterol synthase, is also reported [ 25 ]. Therefore, the inhibitory effect of HMG-CoA reductase is considered to be one of the mechanisms of cholesterol reduction by propolis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, likely to this study, the improvement of cholesterol level was observed by administering propolis to rats, which supports and is consistent with the results of this study [ 24 ]. In the same paper, the inhibitory effect of hydroxymethylglutaryl-CoA (HMG-CoA) reductase, a cholesterol synthase, is also reported [ 25 ]. Therefore, the inhibitory effect of HMG-CoA reductase is considered to be one of the mechanisms of cholesterol reduction by propolis.…”
Section: Discussionmentioning
confidence: 99%
“…LDL-C is seen to cause vascular and neurotoxic effects in the brain [ 35 , 36 ]. Another study by Zhon, a systematic review including nearly 6500 patients, found the same association; however, LDL-C was high in patients with AD mostly around 60-70 years of age, gradually reduced with ageing [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is an approach that aims to offer a new perspective of secondary research (meta-research), a field hallmarked by the need to provide the most integrated evidence possible, and in which several novel study designs have appeared during the last years, e.g., series of systematic reviews and meta-analyses in a single Abbreviations: BMI body mass index, OR odds ratio, RR relative risk, 95% CI 95% confidence interval Note: In this table, only statistically significant risk factors that appeared in more than two studies were included publication, where the analytical unit is the umbrella review study design [88]. Likewise, other attempts refer to field-wide meta-analyses, in which a meta-analysis of observational studies is conducted on the sum of risk factors under consideration [87], or to the synthesis of systematic reviews (e.g., in Neurology [89]), systematic reviews of systematic reviews [90], overviews of systematic reviews [91], meta-reviews [92], systematic meta-reviews, comprehensive reviews [93], research-on-research [94], and meta-meta-analyses [95,96]; these are all terms and study designs that future meta-umbrella reviews should include in their search strategy. Therefore, our metaumbrella review could represent another study design added to the armamentarium of meta-research [97].…”
Section: Discussionmentioning
confidence: 99%